2008
DOI: 10.1124/jpet.108.143826
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced CXC-Chemokine/CXC-Chemokine Receptor Signaling in Metastatic Prostate Cancer Cells Confers Resistance to Oxaliplatin through Potentiation of Nuclear Factor-κB Transcription and Evasion of Apoptosis

Abstract: Constitutive activation of nuclear factor (NF)-B is linked with the intrinsic resistance of androgen-independent prostate cancer (AIPC) to cytotoxic chemotherapy. Interleukin-8 (CXCL8) is a transcriptional target of NF-B whose expression is elevated in AIPC. This study sought to determine the significance of CXCL8 signaling in regulating the response of AIPC cells to oxaliplatin, a drug whose activity is reportedly sensitive to NF-B activity. Administration of oxaliplatin to PC3 and DU145 cells increased NF-B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 33 publications
8
92
1
3
Order By: Relevance
“…However, co-administration of DEX was observed to attenuate the docetaxel-induced AP-1 and NF-kB transcriptional activity and abrogated docetaxel-induced CXC-chemokine gene transcription and secretion in PC3 cells and endothelial cells. We have recently reported that the induction of IL-8 signalling in hypoxic and normoxic CaP cell lines activates cell survival signalling and confers a survival advantage to these cells in response to DNAdamage agents (Maxwell et al, 2007;Wilson et al, 2008b), antiandrogens and biological inducers of apoptosis such as TNF-receptor apoptosis-inducing ligand (Wilson et al, 2008a). Direct inhibition of NF-kB using BAY11-7082 or direct antagonism of IL-8 signalling, targeting the ligand with a neutralising antibody or through a CXCR2-receptor antagonist, failed to potentiate the cytotoxicity of docetaxel in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, co-administration of DEX was observed to attenuate the docetaxel-induced AP-1 and NF-kB transcriptional activity and abrogated docetaxel-induced CXC-chemokine gene transcription and secretion in PC3 cells and endothelial cells. We have recently reported that the induction of IL-8 signalling in hypoxic and normoxic CaP cell lines activates cell survival signalling and confers a survival advantage to these cells in response to DNAdamage agents (Maxwell et al, 2007;Wilson et al, 2008b), antiandrogens and biological inducers of apoptosis such as TNF-receptor apoptosis-inducing ligand (Wilson et al, 2008a). Direct inhibition of NF-kB using BAY11-7082 or direct antagonism of IL-8 signalling, targeting the ligand with a neutralising antibody or through a CXCR2-receptor antagonist, failed to potentiate the cytotoxicity of docetaxel in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…To see whether MT1G expression altered this signaling pathway, we measured mRNA levels of two known NF-kB target genes involved in chemoresistance [interleukin (IL)-8 and CXCL1; ref. 25] after OXA treatment of MOCK and MT1G þ cells. As shown in Fig.…”
Section: Chemotherapy Treatment Modulates Zinc Metabolismmentioning
confidence: 99%
“…We, along with others, have shown that CXCL8 signalling contributes to the transition of a disease to a castration-resistant state (Araki et al, 2007;Seaton et al, 2008). Furthermore, we have shown that CXC-chemokine signalling (including CXCL8) modulates the sensitivity of CaP cells to environmental stresses such as hypoxia and chemotherapy agents, including the DNA-damage agents oxaliplatin and etoposide Wilson et al, 2008a).…”
mentioning
confidence: 95%
“…RNA was harvested and prepared for analysis by quantitative realtime (qPCR) as previously described (Wilson et al, 2008a). The cDNA (50 ng) was mixed with primers (2 nM), sterile water and SYBR Green PCR mastermix (Finnzymes Diagnostics, Espoo, Finland).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation